Amniotic membrane transplantation: Current indications in a tertiary eye hospital of eastern Nepal - Hamal, Diwa; Singh, Sanjay Kumar; Lamichhane, Binaya; Sharma, Archana; Anwar, Afaque; Mahaseth, Vijay (Nepalese Journal of Ophthalmology, 2017)
Introduction: Amniotic membrane has unique properties that can be helpful to treat different ocular surface diseases. Objectives: To report our experience with 100% glycerol preserved amniotic membrane at 4°C and fresh amniotic membrane transplantation (AMT) with and without limbal graft for ocular surface reconstruction. Materials and methods: Retrospective case study of 211 eyes of 211 patients was conducted at Biratnagar Eye Hospital from June 2008 to March 2014. The cases were evaluated in terms of demographic parameters, preoperative diagnosis and the type of surgery performed. Results: The most common indication for surgery was Pterygium (90 eyes, 42.65%), followed by symblepharon (57 eyes, 27.01%), chemical injury (35 eyes, 16.58%), socket reconstruction (9 eyes, 4.26%), shield ulcer (6 eyes, 2.84%), PED (4 eyes, 1.89%), Steven Jonson’s syndrome (5 eyes, 2.36%), dry Eye (2 eyes, 0.94%), Corneal Degeneration (2 eyes, 0.94%), bullous keratopathy (1 eye, 0.47%). The mean age was 28.12 ±17.2 years (age range 3-78 years). More men (161, 76.30%) underwent surgery than women (50 eyes, 23.69%). Symblepharon (24 eyes, 36.36%) was the major cause of surgery in pediatric group. The mean follow-up was 7 months (range 2-36, months). Resurgery was needed in (18 eyes, 8.53%) of which symblepharon (7eyes, 39%) was the major cause. AMT was done in 189 (89.57%) eyes and AMT with conjunctival limbal graft was done in 22(10.42 %) cases. Infectious, inflammatory, or allergic reactions were not encountered in any patient. Conclusion: All patient experienced increased ocular comfort with anatomical restoration of corneal and conjunctival surfaces. AMT alone or in combination with limbal graft aids in ocular surface reconstruction.